Investigating the influence of pollen sources on fruit traits of date palm (Phoenix dactylifera) cv. Barhee in hot arid condition (Indian Journal of Arid Horticulture, 2025)
Date palm is a dioecious species thus the commercial cultivation of date palm depends on the efficient pollination process to achieve higher fruit set and quality. This research experiment was conducted at ICAR-Central Institute for Arid Horticulture, Bikaner during 2021 and 2022 to investigate the effects of different male date palm (M1, M2, M3 and Ghanami) on various fruit traits, yield and total soluble solids of date palm variety Barhee. Among the four pollen sources, M1 resulted in the highest number of berries per strand, lowest fruit drop percentage, maximum fruit bunch weight, fruit length, fruit width and yield. The TSS percentage was higher when pollens from M1 were used compared to others. The study suggests that the selection of pollen source plays a crucial role in determining the yield and quality of date palm variety Barhee. These findings can be useful for the cultivation and breeding of date palm trees, especially for improving fruit yield and quality.